Continuing wildlife population declines and range contraction in the Mara region of Kenya during 1977-2009 - Ogutu, Joseph O.; Owen-Smith, N.; Piepho, Hans-Peter; Said, Mohammed Yahya (Wiley, 2011)
Populations of many wild ungulate species in Africa are in decline largely because of land-use changes and other human activities. Analyses that document these declines and advance our understanding of their underlying causes are fundamental to effective management and conservation of wild ungulates. We analyzed temporal trends in wildlife and livestock population abundances in the Mara region of Kenya. We found that wildlife populations in the Mara region declined progressively after 1977, with few exceptions. Populations of almost all wildlife species have declined to a third or less of their former abundance both in the protected Masai Mara National Reserve and in the adjoining pastoral ranches. Human influences appeared to be the fundamental cause. Besides reinforced anti-poaching patrols, the expansion of cultivation, settlements and fences and livestock stocking levels on the pastoral ranches need to be regulated to avoid further declines in the wildlife resource.